2017
DOI: 10.18240/ijo.2017.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of matrix metalloproteinases 1 and 3 and their tissue inhibitors in the conjunctival tissue and fibroblasts cultured from conjunctivochalasis

Abstract: The overexpression of MMP-1 and MMP-3 in conjunctival tissue and fibroblasts may play an important role in the pathogenesis and development of CCh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…While CCH has been a recognized pathology since 1908, only during the last several years have there been attempts to investigate the condition and its role in the pathogenesis of dry eye syndrome [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…While CCH has been a recognized pathology since 1908, only during the last several years have there been attempts to investigate the condition and its role in the pathogenesis of dry eye syndrome [ 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent transcriptome analysis of human conjunctiva with CCh demonstrated that reduced gene expression could cause decreased cell viability, which is related to the aging process 26 . The second is OS inflammation, which induces elastic fiber breakdown by destructive fibroblasts and infiltrated cells, resulting in initiating or accelerating CCh 13 , 14 , 27 – 29 . Proinflammatory proteins also have been detected in tears of CCh patients 15 , 30 32 .…”
Section: Discussionmentioning
confidence: 99%
“…CCh is often found between the globe and lower eyelid, but in severe cases can be observed in the superior and even the whole bulbar conjunctiva 2 , 12 . CCh has been thought to be caused by elastic fiber degradation involving inflammatory factors or mechanical interference with conjunctival lymphatic circulation 13 15 . Recently, CCh is considered to be one of the friction-related diseases (FRD), which also include superior limbic keratoconjunctivitis and lid wiper epitheliopathy 16 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these cytokines may locally induce matrix metalloproteinase (MMPs) or serine protease activity, which may directly or indirectly modulate ECM protein production or their destruction [4,19,20]. Inflammation has also been shown to alter the expression of MMPs or serine proteases in the conjunctival tissue, which may initiate collagenous fibre melting [21]. In our study, we found that the presence of collagen type I does not significantly change urokinase-type plasminogen activator (uPA) and its receptor (uPAR) production in the co-culture models.…”
Section: Discussionmentioning
confidence: 99%